The development of functional-technological model of “ехtrасtum rubiae tinctоrum siccum” production - E. Yu. Bulychev; V. V. Burlyaev; E. V. Burlyaeva; P. V. Krutov (Тонкие химические технологии)
We provide a formal description of “ехtrасtum rubiae tinctоrum siccum” production by means of functional modeling. The result of such description is a functional-technological mode that is a graphical representation of technological, decision making and quality test processes. The model is provided by IDEF0 functional modeling notation. We describe inputs, outputs, mechanisms and controls for all the processes focusing on the modeling of feedbacks that describe reagent recycling. The model should assist in system analysis of the herbal medicinal products manufacturing. It is the first step of the informational support of the manufacturing process.